Exploring the role of date pit based drinks against hyperglycemia and hypercholesterolemia - Ahmed, Aftab; Arshad, Muhammad Umair; Saeed, Farhan; Tufail, Tabussam (Progress in Nutrition, 2019)
Background: The current study was used to probe the nutraceutical drinks containing Ajwa date pit powder against hyperglycemia and hypercholesterolemia. For this purpose, bio-evaluation studies were carried out on biochemical parameters in rodent modeling by using Ajwa roasted date pit drink. Methods: The Ajwa roasted date pit drink was developed under the aegis of a commercial automatic brewing machine and analyzed for sensorial and nutritional attributes. Moreover, effects of drinks on cholesterol and blood glucose levels in albino rats were explicated through efficacy studies. The collected data was subjected to statistical analysis using completely randomized design (CRD) through statistical through software Minitab 16. Results: Data reported that drink containing 5 and 10% Ajwa roasted date pit powder showed the maximum reduction in cholesterol, LDL and triglycerides 13.20, 15.23 and 9.13%, followed 8.01, 8.63 and 6.77%. Similarly, resultant drinks diminished the blood glucose level as 7.12 and 10.23% consecutively. These drinks also enhanced the insulin concentration as 7.56 and 3.25% in hyperglycemic rats. Conclusion: It is perceived that Ajwa date pit is endowed with vivid forthcoming to ameliorate the effect of oxidative stress, thus stopping the chain reactions implicated in the onset of chronic diseases. The outcomes of current project found Ajwa date pit most effective against obesity and allied discrepancies including hyperglycemia and hypercholesterolemia. Nutraceutical drinks have been proven significantly effective to reduce the glucose and cholesterol levels in experimental animals.